Write great ads. A step-by-step approach - Levy Klein Erica
Write great ads takes you, step-by step, through very aspect of the process. Youll learn. How to zero in on the key features and benefits of your had. How to write a headline that really sells. How to come up white an original, effective selling concept. How to put all the facts together and craft an irresistible call to action- guaranteed to pull in sales.
Introductión. Take advertising one step a time. Beat the " Mabe Im not creative enough" Blues. Homework, legwork, and research: How to avoid copy that doesnt sell. Ive got this ad to write-Now what?. Develop a concept. Feature creature versus benefits champ. The Anatomy of an ad. Create the feadline. Billboard writing: Copywriting at 55 miles per hour. Subheads- the underrated secondary headline. Sexi body copy. Accentuate the positive. Closing arguments/Call to action. Showtime! Put it all together and write your first ad. Gear up to write a longer ad. Now, tacklea brochure. Take the direct approach with direct mail. Ligths ! camera! tv!. Tuning in for radio. Clear your " voice". Some great consumer advertising. Some great business-to-Businee advertising. Some great fund raising advertising. Some great financial advertising. Some great health care advertising. Some great retail advertising. Some great subscription advertising. If you want to write advertising all day... and sometimes all nigth: Thoughts on becoming an avertising copywriter. Glossary of advertising terms. Bibliography. Index.
Keywords: Publicidad directa